Clinical Management of Patients with Heart Failure (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint comprises chapters describing new diagnostic approaches, risk assessment strategies, challenges encountered in peculiar patients, innovative drug therapies, and invasive procedural options. It starts by pointing out the prognostic value of several biomarkers for diagnosis, risk stratification, and follow-up of patients with heart failure. Another aspect is the significance of genetic mutations in patients with life-threatening arrhythmias. Other points of interest in this reprint concern a more accurate evaluation of left ventricular systolic function that involves non-invasive methods (transthoracic echocardiography and electrocardiography Holter monitoring). Then, this reprint continues by highlighting the important contribution of various cardiovascular complications and comorbidities severely impacting the outcome of patients with heart failure. Another section of this reprint is dedicated to the therapy of chronic heart failure, starting with the importance of non-pharmacological methods and identifying patients with difficulties in their self-management that have resulted in compliance issues. Regarding therapy, special emphasis is given first to optimizing medication and, on the other hand, to employing left ventricular assistance devices, where necessary, or mechanical cardiocirculatory support as a bridge preceding cardiac transplantation. Finally, a special matter of concern is the treatment of acute heart failure where therapeutic strategies are less standardized.